PERAN AUDIT KEUANGAN INTERNAL SEBAGAI ALAT PENGENDALIAN DAN EVALUASI MANAJEMEN KEUANGAN PADA UMKM JASA DARAUGIIART - Ummul Bisriah Fatrah; Rini Bella Vista; Fitri Faizah Nayanty; Muhammad Arya Rezqy Firmansyah; Madi, Ahmad Siddiq (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the role of internal financial auditing as a tool for financial management control and performance evaluation in the UMKM (Micro, Small, and Medium Enterprise) Jasa Daraugiart. The research focuses on the implementation of internal financial audits, their effectiveness in supporting cash flow control, and their contribution to improving the quality of financial performance evaluation. This study employs a qualitative descriptive approach, with data collected through semi-structured interviews, direct observation of recording and transaction processes, and documentation of financial records. The findings indicate that the internal audit practices within Jasa Daraugiart remain simple and are not yet formally structured; however, they still play a significant role in maintaining the accuracy of revenue recording, reconciling financial data, and detecting discrepancies in transactions. Internal audits also contribute to identifying seasonal income patterns, assessing the effectiveness of operational expenditures, and strengthening accountability through the separation of business and personal accounts. Although the recording of expenses is not yet optimal and functional segregation remains limited, internal auditing is shown to enhance the effectiveness of financial management control and provide a more accurate basis for decision-making. These findings affirm that even a basic internal audit system serves as a strategic instrument for improving the quality of financial governance in UMKM.